Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.1002/biof.1244
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin inhibits B[a]PDE‐induced procarcinogenic signals in lung cancer cells, and curbs B[a]P‐induced mutagenesis and lung carcinogenesis

Abstract: Benzo[a]pyrene is a procarcinogen present in environment and cigarette smoke, which could be bio-transformed in vivo to B[a]PDE, a potent carcinogen known to form DNA adducts and induce mutations. We observed that curcumin, a known chemopreventive, could significantly inhibit the survival of lung cancer cells exposed to B[a]PDE. It also downregulates B[a]PDE-induced nuclear translocation of NF-κB as assessed by Electrophoretic Mobility Shift Assay (EMSA) and NF-κB-dependent reporter gene assay. Ames assay demo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 42 publications
(52 reference statements)
1
17
0
Order By: Relevance
“…Curcumin is a chemopreventive agent, which possesses multifaceted potentials to prevent cancer progression (15). There are several studies demonstrating the efficacy of curcumin in preventing cancer progression induced by protumorigenic agents and environmental mutagens (16,17). Several reports, including those from our laboratory, have shown the chemopreventive efficacy of curcumin against lung cancer (17,18).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Curcumin is a chemopreventive agent, which possesses multifaceted potentials to prevent cancer progression (15). There are several studies demonstrating the efficacy of curcumin in preventing cancer progression induced by protumorigenic agents and environmental mutagens (16,17). Several reports, including those from our laboratory, have shown the chemopreventive efficacy of curcumin against lung cancer (17,18).…”
Section: Introductionmentioning
confidence: 99%
“…There are several studies demonstrating the efficacy of curcumin in preventing cancer progression induced by protumorigenic agents and environmental mutagens (16,17). Several reports, including those from our laboratory, have shown the chemopreventive efficacy of curcumin against lung cancer (17,18). Although there are ample reports highlighting the anticancer potential of curcumin, the major hindrance in employing it for cancer therapy and prevention, stems from its poor aqueous solubility and bioavailability (19).…”
Section: Introductionmentioning
confidence: 99%
“…However, in most cancers including hepatocellular carcinoma, it is constitutively activated . Activation of NF‐κB is most commonly mediated by IκB kinase (IKK) complex which inhibits IκBα by decreasing phosphorylation . Upon phosphorylation of IκBα, NF‐κB dimmers get free and translocated into nucleus where it activates genes that are crucial for survival, antiapoptosis, drug resistance, angiogenesis, invasion and metastasis .…”
Section: Discussionmentioning
confidence: 99%
“…Activation of NF‐κB is most commonly mediated by IκB kinase (IKK) complex which inhibits IκBα by decreasing phosphorylation . Upon phosphorylation of IκBα, NF‐κB dimmers get free and translocated into nucleus where it activates genes that are crucial for survival, antiapoptosis, drug resistance, angiogenesis, invasion and metastasis . Recent research has shown that NF‐κB is activated in response to prevailing chemotherapeutic drugs which plays a vital role in poor prognosis of various cancers including liver cancer .…”
Section: Discussionmentioning
confidence: 99%
“…Apart from the studies aiming at analyzing the influence of individual products with a specific content on the cascade of changes induced by BaP, there are many papers describing the influence of isolated single compounds, such as vitamin C, β-carotenoids, retinol, retinoic acid, phenethyl isothiocyanate, luteolin, chrysin, naringenin, quercetin, damnacanthal, proanthocyanidine, resveratrol, berberine, catechin, anthocyanins, apigenin or kaempferol. The mechanisms of action of the selected phytochemicals and the above-mentioned dietary compounds are presented in Table 1 [52][53][54][55][56][57][59][60][61][62][63][64][65][66][67][68][69][70][71][72][73].…”
Section: Benzo(a)pyrene (Bap)mentioning
confidence: 99%